Pengaruh Intellectual Capital, Islamic Corporate Social Responsibility, dan Islamic Corporate Governance Terhadap Kinerja Perbankan Syariah di Indonesia Periode 2016-2018 - Novi Tri Astuti; Siti Suharni (Universitas Merdeka Madiun, 2020)
Abstract— This study aims to examine the influence of Intellectual Capital, Islamic Corporate Social Responsibility, and Islamic Corporate Governance on the Performance of Islamic Banking in Indonesia. Technique in intake of sample use method of purposive sampling. Data obtained from the secondary data is the annual report of 11 Islamic Commercial Banks in Indonesia registered in OJK over a period of years 2016-2018. Data analysis was done with a doble linier regression with SPSS program version 16.00 for windows. The results showed that the variable Intellectual Capital has significantly affect on financial performance of Islamic Banking in Indonesia 2016-2018 Period. While the variables Islamic Corporate Social Responsibility and Islamic Corporate Governance is no significantly affect on financial performamce.of Islamic Banking in Indonesia 2016-2018 Period. Keywords—: Intellectual Capital; Islamic Corporate Social Responsibility; Islamic Corporate Governance; Performance of Islamic Banking.